2018
DOI: 10.1038/s41413-018-0035-6
|View full text |Cite|
|
Sign up to set email alerts
|

RANKL signaling in bone marrow mesenchymal stem cells negatively regulates osteoblastic bone formation

Abstract: RANKL signaling is essential for osteoclastogenesis. Its role in osteoblastic differentiation and bone formation is unknown. Here we demonstrate that RANK is expressed at an early stage of bone marrow mesenchymal stem cells (BMSCs) during osteogenic differentiation in both mice and human and decreased rapidly. RANKL signaling inhibits osteogenesis by promoting β-catenin degradation and inhibiting its synthesis. In contrast, RANKL signaling has no significant effects on adipogenesis of BMSCs. Interestingly, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
108
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(112 citation statements)
references
References 27 publications
(26 reference statements)
2
108
2
Order By: Relevance
“…Bone homeostasis was maintained by bone‐resorbing osteoclasts and bone‐forming osteoblasts . RANKL has been revealed to be associated with osteoporosis in postmenopausal women . An experiment had stated that RANKL can stimulate osteoclast formation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone homeostasis was maintained by bone‐resorbing osteoclasts and bone‐forming osteoblasts . RANKL has been revealed to be associated with osteoporosis in postmenopausal women . An experiment had stated that RANKL can stimulate osteoclast formation .…”
Section: Discussionmentioning
confidence: 99%
“…31 RANKL has been revealed to be associated with osteoporosis in postmenopausal women. 32,33 An experiment had stated that RANKL can stimulate osteoclast formation. 34 Another study has illustrated that osteoclastogenesis, bone resorption and osteoclast activities are inhibited through suppression of RANKL pathway.…”
Section: Discussionmentioning
confidence: 99%
“…RANKL, a transmembrane protein from the tumor necrosis factor (TNF) superfamily, is able to bind RANK on the surface of osteoclast precursors to trigger osteoclastogenesis . Chen et al discovered that RANKL signaling inhibits osteogenesis by promoting β‐catenin degradation and inhibiting its synthesis, which further suppresses osteogenic differentiation of BMSC. Xiong et al found that soluble RANKL contributes to osteoclast formation in adult mice.…”
Section: Mechanisms Underlying Melatonin's Action On Osteoporosismentioning
confidence: 99%
“…Certain bone anabolic agents, such as PTH, recombinant human growth factors, and platelet-rich concentrates, as well as the major antiresorption medications, namely, bisphosphonates (BPs), have already been showed to be effective in regenerating periodontal bone [1,7]. Moreover, since bone formation and resorption are coupled and coordinated with each other, concurrent application of anabolic and antiresorption agents are introduced in regenerative periodontology very recently [8][9][10]. However, there is a lack of evidence-based studies to answer whether this synergistic way was superior to single application until now.…”
Section: Introductionmentioning
confidence: 99%